1955
DOI: 10.1017/s0021859600039654
|View full text |Cite
|
Sign up to set email alerts
|

Studies on milk production of Large White pigs

Abstract: 1. A review of the literature relating to the frequency at which pigs suckle under natural conditions was made. The evidence indicated that the average interval between successive sucklings is approximately 1–1¼ hr.2. A number of sows and their litters were continuously observed for varying periods of time under natural conditions and a similar average interval between sucklings was observed.3. A review of the literature relating to the determination of milk production of sows was made. This showed that the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 11 publications
(8 reference statements)
8
51
0
Order By: Relevance
“…However, between birth and weaning, the piglets that suckled anterior teats gained more weight than the other piglets, confirming results from other studies (FRASER & JONES, 1975;PLUSKE et al, 2007;SKOK et al, 2007;PEDERSEN et al, 2011). This can be attributed to a greater milk intake after birth in piglets that suckle anterior teats, as it has been shown that the anterior mammary glands of the sow tend to produce more milk than the posterior ones (BARBER et al, 1955;SKOK et al, 2007), and there is a correlation between milk intake and growth of piglets until the third week of nursing (BARBER et al, 1955). In contrast, it is unlikely that the greater weight gain of AT piglets is due to differences in feed intake, as this is very low in suckling piglets during their first weeks of life.…”
Section: Discussionsupporting
confidence: 87%
“…However, between birth and weaning, the piglets that suckled anterior teats gained more weight than the other piglets, confirming results from other studies (FRASER & JONES, 1975;PLUSKE et al, 2007;SKOK et al, 2007;PEDERSEN et al, 2011). This can be attributed to a greater milk intake after birth in piglets that suckle anterior teats, as it has been shown that the anterior mammary glands of the sow tend to produce more milk than the posterior ones (BARBER et al, 1955;SKOK et al, 2007), and there is a correlation between milk intake and growth of piglets until the third week of nursing (BARBER et al, 1955). In contrast, it is unlikely that the greater weight gain of AT piglets is due to differences in feed intake, as this is very low in suckling piglets during their first weeks of life.…”
Section: Discussionsupporting
confidence: 87%
“…In these instances we never observed a milk ejection. One of the most notable deviations from the usual pattern was 'incomplete suckling', which has been defined as apparetly normal suckling which does not lead to milk ejection (Barber, Braude & Mitchell, 1955;Whittemore & Fraser, 1974). Identification of 'incomplete suckling' has so far been based on behavioural observations or by attempts to milk the udder manually.…”
Section: Resultsmentioning
confidence: 99%
“…Suckled by the sow, piglets developed a rigid nutritional stereotype divided into three to five phases, recurring at about 1-h intervals, soon after birth. They suck milk under active participation of the sow only during one phase lasting merely 13 to 37 s (Barber et al 1955;Gill and Thompson 1956;Whittemore and Frazer 1974;Newberry and Wood-Gush 1985;Holub 1988;Jensen 1988). From 3 to 5 days of age, however, they not only suck water in milk but also drink it from watering installations (Groth 1980) similarly to grown-up pigs.…”
Section: Nutrition Milk Supplementary Feeding Liquid Diet Early Wmentioning
confidence: 99%
“…Under such rearing practices their total water intake increases from 481 (in the 1st week) to 1729 g. d-l (in the 8th week) (Aumaitre 1964(Aumaitre , 1965. However, the consumption of free water by drinking is lower (Bauer et al 1978;W6jcik et al 1978;Bauer 1983, Fraser et al 1988.…”
Section: Nutrition Milk Supplementary Feeding Liquid Diet Early Wmentioning
confidence: 99%